Lead Free Multilayer Piezoelectric Actuators by Economically New Approach - Hussain, Fayaz; Khesro, Amir; Lu, Zhilun; Wang, Ge; Wang, Dawei (Frontiers in Materials, 2020)
The replacement of PZT with a PbO-free alternative is the subject of intense investigation worldwide. In this research, a cheap reliable methodology for the fabrication of multilayers (MLs) of lead-free potassium sodium niobate (KNN)-based ceramics is presented without the need for vacuuming and/or hot isostatic pressing of the tape. The thickness per active layer was 193μm and 102μm for the 10 and 16 layer MLs actuators, respectively. Effective d33 (piezoelectric coefficient), effective d33*, bi-polar strain (Smax), max displacement, dielectric constant (ɛr)and loss (tanδ) are 2500pC/N, 4604pm/V, 0.17%, 2.2μm, 1812 and 2% at 1kHz, respectively, where the effective d33 or d33* is the total output of all layers together. The ultimate target materials for potential substitution with KNN-based ceramics and MLs are commercial PZT-4 and PZT-8.